Is Multiparity in Adolescent Pregnancies Associated with Adverse Outcome? - Turgal, Mert; Seven, Banu; Icer, Bilal; Gultekin, Ismail Burak; Kucukozkan, Tuncay (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objective: Aim of this study was to compare the maternal and neonatal outcomes between adolescent multiparas and adults. Study Design: This retrospective cohort study included over 11 years and singleton multiparous pregnancies from women less than 29 years admitted for delivery after 22nd gestational weeks in tertiary educational hospital. All of patients were divided into two groups as adolescent multipara (under 18 years) and control (19-29 years). Pregnancy outcome and perinatal complications were evaluated. Mann-Whitney U-test, Independent sample t test, Pearson Chi-square test and Fisher Exact test were used for statistical analyses. Results: Gestational week at delivery was significantly lower in adolescent multipara group (38.37 ± 2.17) than control group (38.79 ± 1.684) (p=0.014). Preterm birth rate (12.6%) and postpartum hemorrhage (5.7%) were higher in the adolescent multipara group than in controls as to be statistically significant. The cesarean delivery rate and other pregnancy complications such as diabetes mellitus, preeclampsia, intrauterine growth restriction, oligohydramnios, polyhydramnios, and placental abruption were similar with controls. Conclusion: In conclusion, adolescent multipara pregnancies were associated with higher risks of adverse pregnancy outcomes, in particular preterm birth, lower birthweight and postpartum hemorrhage.